2022
DOI: 10.1097/jpa.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Mental Health Among Physician Assistant Students with Shared Living Experiences Through Synchronous Videoconferencing

Abstract: Purpose We tested the hypothesis that physician assistant (PA) students can benefit from exposure to senior PAs who share their living experiences with mental illness.Methods First-year students from 5 PA programs were asked to participate in this mixed methods study. After completing a pre-activity survey, students from 3 programs participated in an intervention consisting of senior PA faculty sharing their mental health experiences, including treatment and recovery. A facilitated discussion followed, and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…A study of first-year PA students showed that interventions such as senior PAs sharing their personal experiences with mental illness and facilitated discussions with open reflection are effective at reducing stigma. 20 Given the increased risk of mental illness in PA students, programs should consider adding similar programs to de-stigmatize mental health as well as other strategies to improve mental well-being.…”
Section: Practices To Improve Mental Healthmentioning
confidence: 99%
“…A study of first-year PA students showed that interventions such as senior PAs sharing their personal experiences with mental illness and facilitated discussions with open reflection are effective at reducing stigma. 20 Given the increased risk of mental illness in PA students, programs should consider adding similar programs to de-stigmatize mental health as well as other strategies to improve mental well-being.…”
Section: Practices To Improve Mental Healthmentioning
confidence: 99%
“…The course began in the fifth week of each program's didactic curriculum, a timeline based on feedback from prior studies performed by the research team. 5,6…”
Section: Course Structurementioning
confidence: 99%
“…5 One such study showed that disclosure of lived experiences of mental illness by practicing providers improved the help-seeking behaviors of medical students, and this has been successfully replicated in PA programs. 5 Additionally, mindfulness has been shown to increase resilience to stress in university students and brief curricular exposure to mindfulness and decentering content has been shown to improve PA students' levels of mindfulness, which significantly predicted change in life satisfaction and perceived stress. 6 Likewise, narrative writing has been shown to provide a space to relate self-reflection with clinical practice.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations